Prenatal Perfluorooctanoic Acid (PFOA) exposure causes reproductive toxicity by disrupting the formation of transzonal projections (TZPs) and down-regulating Wnt4/β-catenin signaling pathway in progeny - Hua Du; Lishuang Song; Min Zhao; Xiaorong Zhao; Ren Mu; Shengtao Gao; Bin Zhang; Jiapeng Wang (Ecotoxicology and Environmental Safety)
Perfluorooctanoic acid (PFOA) has been recognized as a novel persistent organic pollutant, playing a significant role in global environmental contamination. Recent evidence indicates that exposure to PFOA detrimentally affects reproductive function, notably through a progressive decline in ovarian function. However, there is a notable lack of research specifically examining its impact on the reproductive potential of female offspring. In this study, we report that prenatal exposure to PFOA impairs the competence of maturing oocytes and reduces the yield of oocytes in the progeny. Mechanistically, prenatal exposure to PFOA leads to a reduced expression of Wnt4, which subsequently impairs the integrity of the ovarian follicle basement membrane and decreases the expression of proteins related to adherent junctions in granulosa cells. This cascade of events results in a compromised reduction of transzonal projections (TZPs) within ovarian follicles, ultimately leading to mitochondrial dysfunction and diminished ATP synthesis in oocytes. This study offers comprehensive insights into the underlying mechanisms of PFOA-induced reproductive toxicity and furnishes scientific evidence to support initiatives focused on preventing and mitigating reproductive harm associated with perfluorinated compounds.